Opportunistic Osteoporosis Screening Reveals Low Bone Density in Patients With Screw Loosening After Lumbar Semi-Rigid Instrumentation: A Case-Control Study - Löffler, Maximilian T.; Sollmann, Nico; Burian, Egon; Bayat, Amirhossein; Aftahy, Kaywan; Baum, Thomas; Meyer, Bernhard; Ryang, Yu-Mi; Kirschke, Jan S. (Frontiers in Endocrinology, 2021)
Objective: Decreased bone mineral density (BMD) impairs screw purchase in trabecular bone and can cause screw loosening following spinal instrumentation. Existing computed tomography (CT) scans could be used to screen for low BMD without additional costs. Purpose of this case-control study was to investigate the influence of opportunistically assessed BMD on the outcome after spinal surgery with semi-rigid instrumentation for lumbar degenerative instability. Methods: We reviewed consecutive patients that had primary surgery with semi-rigid instrumentation in our hospital. Patients that showed screw loosening in follow-up imaging qualified as cases. Patients that did not show screw loosening or – if no follow-up imaging was available (n = 8) – reported benefit from surgery at least 6 months after primary surgery qualified as controls. Matching criteria were sex, age, and surgical construct. Opportunistic BMD screening was performed at levels L1 to L4 in perioperative CT scans by automatic spine segmentation and using asynchronous calibration. Mean BMD was compared between cases and controls. Area under the curve (AUC) was calculated for BMD as a predictor of screw loosening. Results: Forty-six elderly patients (69.9 ± 9.1 years) – 23 cases and 23 controls – were included. The majority of surgeries involved 3 spinal motion segments (n = 34). Overall, 20 patients had low bone mass and 13 had osteoporosis according to BMD. Cases had significantly lower mean BMD (86.5 ± 29.5 mg/cm³) compared to controls (118.2 ± 32.9 mg/cm³, p = 0.001) ), i.e. patients with screw loosening showed reduced BMD. Screw loosening was best predicted by a BMD < 81.8 mg/cm³ (sensitivity = 91.3%, specificity = 56.5%, AUC = 0.769, p = 0.002). Conclusion: Prevalence of osteoporosis or low bone mass (BMD ≤ 120 mg/cm³) was relatively high in our study group of elderly patients undergoing spinal surgery. Screw loosening was associated with BMD close to the threshold for osteoporosis (< 80 mg/cm³). Opportunistic BMD screening in existing CT using the presented approach is feasible yielding valuable information. In knowledge of osteoporotic bone the surgeon might take measures to prevent screw loosening in an effort to increase favorable outcomes.